Evaluation of Bore Pile Integrity Based on UDM (Ultrasonic Drilling Monitor) and PIT (Pile Integrity Test) on the Cibogo Main Bridge of the Bocimi Toll Road Project - Septiani Nur Fadillah; Sudjani (Universitas Bengkulu, 2026)
This study aims to determine the condition of the bore pile hole based on the test results and to determine the integrity of the bore pile based on the results of the PIT test on the Cibogo Main Bridge, Bocimi Toll Project. The data collection techniques used in this study by the author are observation, interview, document review, and literature review. The results of the study are at points P05-B06 and P05-B30 which have been tested with UDM and PIT tests, it can be evaluated that the UDM of both points meets the maximum limit requirements of 2%, namely 0.23% (X-X') and 0.23% (Y-Y') and 0.64% (X-X') and 0.52% (Y-Y'). Then the PIT test can produce an evaluation that meets the requirements of ASTM D5882-07, namely the integrity of the pile is classified as Class I, which means Good Pile, and Class II, which means Slightly Damaged. Keywords: Bore Pile, UDM, PIT